2020
DOI: 10.1152/physiolgenomics.00083.2020
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic signature of fasting in human adipose tissue

Abstract: Little is known about the impact of fasting on gene regulation in human adipose tissue. Accordingly, the objective of this study was to investigate the effects of fasting on adipose tissue gene expression in humans. To that end, subcutaneous adipose tissue biopsies were collected from twenty-three volunteers 2h and 26h after consumption of a standardized meal. For comparison, epididymal adipose tissue was collected from C57Bl/6J mice after a 16h fast and in the ab-libitum fed state. Transcriptome analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Similar transcriptional modifications of DEGs associated with the TCA cycle and other energy anabolic pathways were also reported in other fish species in response to starvation [7,64,68,80]. Therefore, these transcriptional decreases in metabolic pathways might indicate a decreased reliance on ATP for the production of energy-related metabolites during starvation, supporting previous findings in fish and other organisms under fasting conditions [64,81,82].…”
Section: Effects Of Starvation On Transcriptomicsupporting
confidence: 87%
“…Similar transcriptional modifications of DEGs associated with the TCA cycle and other energy anabolic pathways were also reported in other fish species in response to starvation [7,64,68,80]. Therefore, these transcriptional decreases in metabolic pathways might indicate a decreased reliance on ATP for the production of energy-related metabolites during starvation, supporting previous findings in fish and other organisms under fasting conditions [64,81,82].…”
Section: Effects Of Starvation On Transcriptomicsupporting
confidence: 87%
“…Defour et al performed a transcriptome analysis of human subcutaneous adipose tissue (SAT) in response to fasting. They reported modulation of the AMPK γ2 subunit 21 , potentially indicating the presence of a nutritional-dependent expression of γ subunits in humans. In light of these findings, we next used the human genotype tissue expression (GTEx) dataset to evaluate the expression of γ subunits as a function of age.…”
Section: Resultsmentioning
confidence: 99%
“…Popdc2, one of the Popeye domain-containing (Popdc) gene families, was highly expressed particularly in the sinoatrial node of the mouse and represented as a novel arrhythmia gene for cardiac conduction disorders [57,58]. A recent study [59] showed that Popdc2 was a fasting-induced gene, which suggests that the abnormal expression of popdc2 may be related to blood glucose. Trim63, also known as MuRF1, was signi cantly increased not only in cardiac muscle of diabetic mice, but also in diabetic limb muscle and STZ-Diabetes [60,61].…”
Section: Discussionmentioning
confidence: 99%